Sistem Pendukung Keputusan Untuk Pemilihan Hotel di Kota Medan Dengan Menggunakan Metode Simple Additive Weighting - Tjokro, Stanley; Romindo, Romindo (JDMIS: Journal of Data Mining and Information Systems, 2023)
The increasing number of tourist locations in the city of Medan has led to growth in the arrival rate of tourists from abroad, and this has caused the hotel business to also increase rapidly. Even though the hotel business is increasing rapidly, not all tourists want to choose any hotel in the city of Medan, because tourists will still pay attention in terms of price, service, location, stars, and cleanliness, even though there are at least 177 hotels in the city of Medan. To overcome the problem of choosing the right hotel, a decision support system will be made to assist users in selecting hotels, and the system will be designed using the Simple Additive Weighting (SAW) method, which will produce alternatives according to the criteria, values, and weights that have been determined. determined by the users. In collecting data for the system, methods such as surveys, field observations, interviews, and literature studies based on official documents will be used. This website-based decision support system generates output in the form of hotel rankings from highest to lowest level.